Higher Education Offshoring as an Innovative Response to Global Learning Challenges - Damian Kedziora; Elzbieta Klamut; Timo Karri; Andrzej Kraslawski (International School for Social and Business Studies, 2017)
The wide implementation of service offshoring strategies worldwide has been visible and studied mainly in such business domains as information technology, accounting, human resource management and customer care centres. Nonetheless, transferring processes to offshore locations has also been implemented in the higher education sector. Responding to demographic, social and globalization challenges, renowned universities seek for innovative solutions that shall enhance quality and attractiveness of their operations, while strengthening their competitive advantage. The paper examines the case of an American university that conducts degree programmes in European offshore locations, in the light of differences between higher education and standard business offshoring.